Experimental set-up and efficiency evaluation of zero-field-cooled (ZFC) YBCO magnetic bearings - Arsénio, António (2018)
This paper presents the conception, simulation and experimental evaluation of magnetic bearings based on NdFeB magnets and zero-field-cooled (ZFC) YBCO bulk superconductors to replace the bearings of a standard electric machine. Advanced research on HTS magnetic levitation has been carried out for the construction of large scale flywheels or for industry applications. However, those approaches used field-cooled (FC) superconductors, whereas the approach shown in this paper uses ZFC superconductors. Actually, as previously shown by the authors, ZFC implementation presents much less AC losses. The approach in our horizontal flywheel research follows the ZFC-maglev structure, where the linear track was closed into a circular one with the same diameter of the superconductor magnetic bearing. The conception and geometric placement of magnets and superconductors was designed to keep symmetry along the rotating axis and minimizing air gaps. A 3D finite element model was built for simulation and validation of the effectiveness of the solution. Experimental validation was then achieved measuring the balanced and unbalanced rotor lifting and guiding forces.